Experimental realization of a three-dimensional topological insulator, Bi2Te3. - Chen, Y; Analytis, J; Chu, J; Liu, Z; Mo, S; Qi, X; Zhang, H; Lu, D; Dai, X; Fang, Z; Zhang, S; Fisher, I; et al. (2009)
Three-dimensional topological insulators are a new state of quantum matter with a bulk gap and odd number of relativistic Dirac fermions on the surface. By investigating the surface state of Bi2Te3 with angle-resolved photoemission spectroscopy, we demonstrate that the surface state consists of a single nondegenerate Dirac cone. Furthermore, with appropriate hole doping, the Fermi level can be tuned to intersect only the surface states, indicating a full energy gap for the bulk states. Our results establish that Bi2Te3 is a simple model system for the three-dimensional topological insulator with a single Dirac cone on the surface. The large bulk gap of Bi2Te3 also points to promising potential for high-temperature spintronics applications.